Changes in the Urinary Metabolites in Losartan-Treated Spontaneously Hypertensive Rats / Norasikin Ab Azis ...[et al.] - Ab Azis, Norasikin; Ahmad Kamal, Mohd Saleh; Radjeni, Zurain; Mediani, Ahmed; Agarwal, Renu (Universiti Teknologi MARA Cawangan Selangor, 2021)
Introduction: This study examined the association of losartan induced changes in urinary metabolomic profile with the changes in blood pressure (BP) and renin-angiotensin- aldosterone system (RAAS) in spontaneously hypertensive rats (SHR). Methods: Male SHR were administered with either 0.5 mL of distilled water (control group, n=6) or 10 mg.kg-1 of losartan (group 2, n=6) daily by oral gavage for 4 weeks. Body weight, BP, food and water intake were measured weekly. At week 4, urine was collected for urinary electrolyte analysis and metabolite profiling, after which the animals were euthanised by decapitation and blood was collected for analysis of components of RAAS and electrolyte concentrations. Urine metabolite profile of SHR was determined using proton nuclear magnetic resonance (1H-NMR) spectrometry combined with multivariate data analysis. Results: At week 4, losartan-treated SHR had significantly lower BP than non-treated SHR. There were no differences in water and food intake, body weight, serum and urinary electrolyte concentrations or in their urinary excretions between the two groups. No differences were evident in the components of RAAS except that the angiotensinogen level was significantly higher in losartan-treated SHR compared to non-treated SHR. Orthogonal partial least squares discriminant analysis (OPLS- DA) showed clear separation of urinary metabolites between control and losartan-treated SHR. Losartan-treated SHR group was separated from the control group by changes in the intermediates involved in glycine, serine and threonine metabolism. Conclusion: Antihypertensive effect of losartan in SHR seems to be associated with changes in urinary metabolite profile, particularly involving the metabolism of glycine, serine and threonine.